2018
DOI: 10.1097/sga.0000000000000330
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Comparisons Between Asian American and White American Women With Irritable Bowel Syndrome

Abstract: There is little information on racial/ethnic characteristics of patients with irritable bowel syndrome. In this study, we determined whether the severity of symptoms (gastrointestinal, psychological distress), cognitive beliefs about irritable bowel syndrome, and life impacts (life interference, health-related quality of life) differ between Asian American and White American women with irritable bowel syndrome. We also look at the relationships among these variables. Asian American women (N = 21) and age- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Despite no significant differences in abdominal pain and bloating, we cannot rule out that sex hormone changes during the transition to menopause are contributing to differences in overall symptom severity. It should be noted that IBS symptom severity is a global measure that encompasses biopsychosocial factors, possible cultural or racial factors, 59 resource utilization, disease burden, and the individual symptoms of abdominal pain, bloating, and changes in bowel habits 60 . We previously demonstrated that overall IBS symptom severity is related to, but distinct from, HRQOL and is predicted by both GI and extraintestinal symptoms and disease‐specific concerns 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite no significant differences in abdominal pain and bloating, we cannot rule out that sex hormone changes during the transition to menopause are contributing to differences in overall symptom severity. It should be noted that IBS symptom severity is a global measure that encompasses biopsychosocial factors, possible cultural or racial factors, 59 resource utilization, disease burden, and the individual symptoms of abdominal pain, bloating, and changes in bowel habits 60 . We previously demonstrated that overall IBS symptom severity is related to, but distinct from, HRQOL and is predicted by both GI and extraintestinal symptoms and disease‐specific concerns 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The findings that Asians had significantly lower total numbers and lower total severity scores of the total, primary, and/or secondary symptoms than other racial/ethnic groups in Clusters 1 and 2 agree with those reported about Asian women’s general menopausal symptoms and general GI symptoms. The literature has consistently indicated that Asian women tended to be less likely to experience psychological, physical, and psychosomatic symptoms due to their menopausal transition than other racial/ethnic groups (Chuah & Mahadeva, 2018; Han et al, 2018; Stake-Nilsson et al, 2013). Moreover, the literature has indicated that Asians are generally less likely to experience GI symptoms (e.g., moderate/severe abdominal pain, constipation, or diarrhea dominant bowel patterns) than Whites (Han et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The overall IBS symptom severity did not differ, but the reporting of abdominal pain and psychological distress was higher in White compared with Asian American patients, whereas bloating was strongly associated with daily stress in Asian American patients. 14 Another study demonstrated higher perceived stress among White patients with IBS compared with people from racial and ethnic minority groups. 15 IBS, one of the most common DGBI, requires the presence of both abdominal pain and bowel dysfunction.…”
Section: Inclusive Clinical Trials For Disorders Of Gut-brain Interac...mentioning
confidence: 99%